Determinants of Adolescents Well Being - Sheeba Ali (SEISENSE Journal of Management, 2018)
Well-being is a dynamic concept that includes subjective, social, and psychological dimensions as well as health-related behaviors. Adolescents form two-thirds of our population, this is a unique group of people with special needs. The study aims to identify the lifestyle and behavioral patterns of this group and subsequently come up with issues that require special attention. The Competitive environment in every field has propelled maladjustment in different spheres of life such as home, social, health, emotion and educational problems. In order to address adolescents’ psychological issues, it becomes everyone’s responsibility to give assistance to protect the future generation.